Treatment of Water River with Activated Carbon from Coal and Palm Shells as Adsorbent - Sri Lestari; Diana Arfiati; Aniek Masrevaniah; Mochammad Sholichin (Postgraduate School Universitas Brawijaya, 2020)
The treatment of water River Karang Mumus with activated carbon from coal and palm shells as adsorbent was investigated. Water quality parameters treated were DO, BOD, N-total, P-total, and TSS. Coal and palm shells was carbonized at 500oC for 45 minutes to produce activated carbon. The surface morphological of activated carbon was characterized by scanning electron microscopy (SEM). River water treatment data shows a decrease in BOD parameters, N-total, P-total, and TSS. While for DO parameters there is no change. Activated carbon from coal shows the ability to reduce contaminants greater than activated carbon from palm shells.